Análise da aplicabilidade da métrica do Economic Value Added (EVA®) para avaliação de empresas concessionárias: estudo de caso do Rodoanel Oeste SA - Rieger, Mauricio (2020)
In an increasingly competitive market, where financial resources are usually scarce, several companies have been improving their management in order to stand out and / or stay in business. In this scenario, it is essential they have precise management strategies, which can be achieved through performance measurement systems. The choice of the theme of this thesis was, basically, based on the lack of research regarding the analysis and applicability of EVA® for companies in the highway concession sector and the importance of road network systems in the Brazilian economic scenario. Based on the theme choice and justification, the central research question was formulated: does EVA® metrics contribute, in a timely manner, to the evaluation of financial performance and, consequently, to the maximization of the wealth of the partners of concessionary companies? In order to answer the central research question, it was necessary to outline the following specific objectives: report the main concepts about performance indicators, present the concept of EVA® metrics and its components, expose the general characteristics of the company, object of case study, its accounting procedures as well as the necessary adjustments to the model. Afterwards, the Brazilian panorama of the concession sector is narrated and its data is presented, and finally, based on the announced methodological procedures, the calculation of EVA® metrics as well as its components are described, the results are presented and EVA® is compared to Return on Assets (investments) - ROA. At the end of this process, it is noted that traditional accounting, through its data, produces interesting performance measurements, which also facilitate the deepening of the operational analyzes involved. However, they do not reflect the opportunity cost of the shareholders' equity. In contrast, the measurement calculated using EVA® takes into account the cost of capital, and, therefore, can show whether business managers created or destroyed wealth for the shareholder. The case study shows that, during the period under analysis, there was no wealth creation for the CCR Rodoanel shareholders. However, this apparently unfavorable result should be argued very carefully due to the existence of positive values in the Free Cash Flow as well as other relevant factors described in the final considerations. As for the relationship between the aforementioned accounting and financial metrics and their consonance with EVA® metrics, it can be seen that the reduction in wealth destruction that occurred gradually as of 2016 is aligned with the increase in liquidity ratios, similarity with the increase in interest coverage ratios and pace with the increases in ROA ratios